Law Enforcement Against Cyber Crime in the Form of Phishing According to Law Number 1 of 2023 Concerning Criminal Code - Feberman Lahagu; Zetria Erma; Ramadhany Nasution (Fox Justi : Jurnal Ilmu Hukum, 2025)
The development of digital technology has given birth to various forms of cybercrime, one of which is phishing, which is a fraudulent act that utilizes social engineering techniques to steal victims' personal data. This study aims to examine the legal regulation of phishing crimes in Law Number 1 of 2023 concerning the Criminal Code, identify the factors that cause this crime, and evaluate the effectiveness of law enforcement in Indonesia. This research uses a normative juridical method with a legislative approach and document study. The results of the study show that the new Criminal Code has explicitly regulated the crime of phishing through Articles 332, 333, and 334 which include illegal access, destruction of electronic systems, and financial benefits from unauthorized access. However, because the law has not been fully enforced, law enforcement still refers to the ITE Law. The main factors causing the rise of phishing include low digital literacy of the community, limited law enforcement facilities, economic factors, and the sophistication of cybercrime modes. Therefore, there needs to be a synergy between adaptive regulations, increasing public awareness, and strengthening the capacity of law enforcement to face the challenges of cybercrime in the digital era.